2002
DOI: 10.1111/j.1365-2621.2002.tb10305.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining Washing Conditions During the Preparation of Frozen Surimi from Surubí (Pseudoplatystome Coruscans) Using Response Surface Methodology

Abstract: The effect of process temperature (2 to 18 °C), time (1 to 7 min/cycle), and water-mince ratio (2:1 to 8:1) on the quality attributes of surubí (Pseudoplatystoma coruscans) surimi was studied using Response Surface Methodology (RSM). Conditions were identified that allowed to achieve 25% of extracted proteins and a moisture content of 79%, compatible with an acceptable quality of surimi gel. The verification of the prediction models was acceptable. Two cryoprotectant mixtures (sucrose-sorbitol and maltodextrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…This work is based on Floros & Chinnan (1987), Garrote et al. (1993, 1994) and Medina & Garrote (2001). The RSM is a mathematical–statistical tool that gives valuable information with a minimum set of experiences; in fresh green peas this is very important as the harvest period is very short.…”
Section: Methodsmentioning
confidence: 99%
“…This work is based on Floros & Chinnan (1987), Garrote et al. (1993, 1994) and Medina & Garrote (2001). The RSM is a mathematical–statistical tool that gives valuable information with a minimum set of experiences; in fresh green peas this is very important as the harvest period is very short.…”
Section: Methodsmentioning
confidence: 99%
“…In the same way, most of the variables influenced the responses cutting strength and work of shearing; however the quadratic effect of washing cycle time presented the highest significative effect for these responses (Table 4). In their work, Medina and Garrote (2001) reported that the three independent variables have a significant effect on gel strength, and the more relevant ones were the water-mince ratio and the washing cycle time for suribí surimi. Cutting strength and work of shearing can be used to study the mechanical properties of surimi gels.…”
Section: Effect Of Process Variables On the Protein Content Of Mscm Smentioning
confidence: 99%
“…The washing procedure is an important step in producing high-quality surimi (Benjakul et al 1997;Medina and Garrote 2001;Ramadhan et al 2012). Washing removes compounds such as sarcoplasmic proteins, inorganic salts, low-molecular weight substances, lipids, and blood components (Benjakul et al 1998;DeWitt and Morrissey 2002), concentrating myofibrillar proteins, which play an essential role in gel formation, improving gel-forming ability and decreasing protein denaturation during frozen storage (Lee 1984;Lanier 1986;Scott et al 1988), and enhances color and flavor of products (Toyoda et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This work is based on Floros and Chinnan (1987), Garrote, Coutaz, Luna, Silva, andBertone (1993, 1994), and Medina and Garrote (2001).…”
Section: Experimental Designmentioning
confidence: 99%